Socioeconomic and gender disparities in anal cancer diagnosis and treatment. (June 2017) - Celie, Karel-Bart; Jackson, Christopher; Agrawal, Surbhi; Dodhia, Chetan; Guzman, Carlos; Kaufman, Theodor; Hellenthal, Nicholas; Monie, Daphne; Monzon, Jose; Oceguera, Luis
Abstract: Background and objectives: We investigated whether receipt of radiation in patients with anal carcinoma is related to income level and other demographic factors. Methods: The SEER database (1988–2011) was queried and linked to the Area Health Resources File (AHRF). We used logistic regression and Kaplan-Meier analyses to correlate receipt of radiation and overall and cancer-specific survival with tumor stage, age, gender, and income. Results: Of 28, 028 patients with anal cancer, 14, 783 (53%) received radiation. Patients in the lowest quartile for median household income were significantly more likely to present at higher stages, were 1.87 times more likely to receive radiation (95% CI 1.74–2.00, p < 0.001), and 1.27 times more likely to die of anal cancer (95% CI 1.18–1.33, p < 0.001) than those in the highest income quartile. Within most stages, however, the wealthiest patients were more likely to receive radiation therapy than the poorest patients. Additionally, we found that women presented at higher stages (p < 0.001), were 2.67 times more likely to receive radiation (95% CI 2.55–2.81, p < 0.001), and were 1.25 times more likely to die of anal cancer than men (95% CI 1.17–1.32, p < 0.001). Conclusions: Women and poorer patients present with more advanced stages of anal cancer, more commonly receive radiation, and are more likely to die of anal cancer than men and wealthier patients, respectively. Highlights: This is the first study to show diagnosis and treatment disparities in anal cancer. Poorer patients had later stage disease and worse survival than wealthier patients. Poorer patients were less likely to receive radiation therapy than wealthier patients. Women presented with later stage disease and had worse survival than men. Despite worse survival, women received radiation therapy more often than men.